ANDROID-BASED PAYMENT APPLICATION IN MA USB FILIAL MAN BATAM - Jemmy Muhammad (Program Studi Teknik Informatika, 2022)
Education Guidance Contribution is a fund that must be paid by parents of students to be used for the student's educational needs. The tuition fee must be paid every month. Lack of payment information becomes a communication barrier for parents about payments at school, especially tuition payments. Manual data processing is quite complicated and takes a long time. Based on these problems, it is necessary to apply Android-based tuition fees at MA USB FILIAL MAN BATAM. This study uses data collection methods, observation and interviews. In designing the application using SDLC (System Development Life Cycle). This research, which is an android-based payment application, is expected to be able to help parents of students in the process of paying tuition fees at MA USB FILIAL MAN BATAM to make it more accurate and efficient.